Evaluating the Odor Mitigation Effects of Biochar-Enhanced Bedding Materials in a Simulated Bedded Pack Dairy Barn Environment: A Laboratory-Scale Study - Jinho Shin; Daehun Kim; Yangjoon Lee; Seunghun Lee; Riuh Wardhani; Heekwon Ahn (Applied Sciences)
This study evaluated the odor mitigation potential of rice husk biochar in a simulated dairy bedded pack over 21 days. Biochar was incorporated into a dairy manure–sawdust mixture at 5% and 10% dry weight. Emissions of key odorous compounds—ammonia (NH3), sulfur compounds, volatile fatty acids, phenol, p-cresol, and indole—were evaluated. Odor units were assessed to determine perceived odor reduction. Biochar significantly reduced NH3 and dimethyl sulfide (DMS) emissions: NH3 by 27% and 43%, and DMS by 53% and 75%, at 5% and 10% application, respectively. The NH3 reduction was attributed to ammoniacal nitrogen adsorption, while the DMS reduction likely resulted from enhanced air permeability suppressing anaerobic bacterial activity. The 5% biochar treatment, achieving 63% and 70% of the NH3 and DMS reductions attained by the 10% treatment, respectively, offers a more practical and cost-effective option. Other odorous compounds were not significantly affected. A temporary reduction in odor units was observed on day 7. Rice husk biochar contains 14.5% atomic Si, primarily as silica, which supports structural stability but hinders pore development, reducing adsorption efficiency. These findings demonstrate the importance of biochar’s physicochemical properties in odor mitigation. Future research should evaluate long-term field performance, microbial interactions, and silica modification strategies.